Sustainability Assessment of Cooperative-Based Community Forest Management in Bengkalis Regency, Indonesia - Suri Budiasih; Aras Mulyadi; Defri Yoza (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Community Forestry (HKm) is one of the social forestry programs in Indonesia that aims to improve community welfare while maintaining forest sustainability. This study aims to evaluate the sustainability status of HKm managed by the Sri Bina Daerah Consumer Cooperative in Bengkalis Regency, Riau Province. The study was conducted in a 3,235.36-hectare HKm area using a survey method through field observations, interviews, and literature studies. A total of 72 community respondents and four stakeholders were selected purposively. Sustainability analysis was conducted using Multidimensional Scaling (MDS) with a modified Rapid Appraisal for Social Forestry (RAP-SPFA) approach on ecological, economic, and socio-cultural dimensions. The results showed that the ecological dimension had a sustainability index of 61.92 (fairly sustainable), supported by relatively adequate vegetation cover and moderate biodiversity. However, secondary vegetation was still dominated, natural forest was limited, and peat hydrological disturbances occurred due to drainage canals. The socio-cultural dimension obtained an index of 47.44 (less sustainable) due to the community's low dependence on HKm resources and the declining application of local wisdom in forest conservation. The economic dimension had the lowest index at 9.50 (unsustainable), reflecting the low contribution of community forests to community income, limited employment opportunities, and minimal diversification of forest-based businesses. Overall, community forest management still shows disparities across sustainability dimensions, necessitating strengthened community businesses, improved market access, restored peat ecosystems, and enhanced local participation.